Sexuality and fertility of young women suffering from breast cancer - Zielińska, Martyna; Zarankiewicz, Natalia; Kosz, Katarzyna; Kuchnicka, Aleksandra; Aleksandrowicz, Jakub; Książek, Katarzyna; Mojsym-Korybska, Sylwia (Journal of Education, Health and Sport, 2019)
Breast cancer (BC) is the most common malignant tumor among women in the world. In Poland, it is the most commonly diagnosed cancer in women between the age of 25 and 44. The course of the disease in young women is more aggressive. As a result more aggressive anti-cancer therapies are used. BC treatment is associated with the occurrence of numerous adverse effects and long-term complications. Among them, sexuality and fertility disorders deserve special attention in the group of young patients.The aim of this study is to review on the occurrence of sexual dysfunction and fertility disorders among young patients suffering from BC. The impact of BC treatment on the occurrence of these disorders has been analyzed. This review emphasizes also possible methods of sexual dysfunction and potential options of fertility protection which may be used in women who want to get pregnant after the end of the treatment. This review is based on available data from medical publications and guidelines from 1987 to 2019, addressing issues of sexuality and fertility in young patients with breast cancer.Young patients suffering from BC experience a variety of sexuality and fertility disorders. Sexual dysfunction includes among others: reduced libido, dyspareunia and difficulty in reaching an orgasm. The reason of the deterioration of the quality of sexual life is complex. Among the emotional factors, the most important role is played by changes in appearance, such as hair loss or breast amputation. Organic causes include dryness or loss of vaginal elasticity. The risk of fertility disorders is primarily associated with the use of cytotoxic drugs, causing premature ovarian failure and inducing amenorrhea. Chemotherapeutic agents with the highest risk of gonadotoxicity are alkylating drugs. Oncofertility is a branch of medicine combining oncology and reproductive medicine. Fertility protection of women who desire bearing a child after treatment is possible thanks to various methods of preservation. These include cryopreservation of embryos and oocytes, ovarian suppression with the use of GnRH analogs, ovarian transposition, freezing and transplantation of ovarian tissue. The most recommended method is embryo cryopreservation at present. Available data suggest no increased risk of cancer recurrence due to pregnancy in women after BC treatment.